Short Communication: Interaction of Nerve Growth Factor (NGF) and Vascular Endothelial Growth Factor (VEGF) in Healthy Individuals - Groh, Adrian; Jahn, Kirsten; Groeschl, Michael; Hillemacher, Thomas; Kornhuber, Johannes; Bleich, Stefan; Frieling, Helge; Heberlein, Annemarie (Disease Markers, 2019)
NGF and VEGF are known to be involved in different psychiatric diseases. In order to verify hints from basic research that both neurotrophines interact with each other, serum levels of NGF and VEGF were measured in a cohort of 33 healthy individuals and correlated. NGF level was 126.30 pg/mL (+/- 155.43), and VEGF level was 57.28 pg/mL (+/- 44.48). Both factors were significantly correlated, confirming their interaction and legitimising the usage of their respective ratio (0.8 (+/- 0.42)) as a less varying additional marker in prospective studies.
CRIS-Team WoS Importer:2019-12-13